The Antu-List Reconsidered: A Synoptic Reading of Edfu and Athribis Scented Material - Wilde, Heike (Zeitschrift für ägyptische Sprache und Altertumskunde, 2025)
This paper examines parallel inscriptions found in the temples of Edfu and Athribis, which are believed to list various types of myrrh. Central to these inscriptions is the term antu , posited as a categorical descriptor for a group of resins. This paper presents a detailed, synoptic presentation and translation of the inscriptions from both Edfu and Athribis, accompanied by a critical review and analysis of its multiple layers of meaning, encompassing religious, cultic, symbolic, and linguistic dimensions. The investigation serves as a methodological framework for understanding how natural materials were conceptualized and classified in Egyptian textual and cultural contexts.